Heat transfer analysis in a tube contained with louver-punched triangular baffles - Jayranaiwachira, Nuthvipa; Promvonge, Pongjet; Promthaisong, Pitak; Nakhchi, Mahdi Erfanian; Skullong, Sompol (My University, 2024)
The present research assesses the thermal effectiveness of a heat exchange tube incorporating louver-punched triangular baffle (LPTB) vortex generators under turbulent conditions. For Reynolds numbers between 4760 and 29,270, the heat transfer and flow behaviors in the consistent heat-fluxed tube equipped with LPTBs were studied numerically and experimentally. A single baffle height/blockage ratio (b/D = BR = 0.25) and relative baffle pitch (P/D = PR = 1) were used for both baffle attack angles, (α) 30° and 45°, along with three louver size ratios (e/b = LR = 0.24–0.56) as well as five louver angles (θ = 0°, 20°, 30°, 45°, 60°, and 90°). The results show that as the LR and θ values decrease, the Nusselt number (Nu) and friction factor (f) of the LPTB rise owing to the improved fluid mixing process generated by streamwise vortices with stronger turbulence kinetic energy. The LPTB with LR = 0 and θ = 0° provides the greatest f and Nu of about 22.18 and 5.1 times, respectively, although the one with LR = 0.24 and θ = 45° has the largest TEF of about 2.39 and 2.5 for the α = 30° and 45° LPTBs, respectively. Furthermore, an examination into the thermal and flow patterns was conducted through a three-dimensional computation; the validation of the numerical and experimental data yielded satisfactory results. Using measured data, the f and Nu correlations of the α = 30° and 45° LPTBs were additionally established.
Keywords: Heat exchanger; Heat transfer enhancement; Thermal effectiveness; Triangular baffle; Vortex generator